Kegiatan Pengenalan Teknik sipil Kepada Generasi A dan Spirit Ramdhan di Masjid Imaduddin Medokan Ayu Rungkut-Surabaya - Ach Nur Irchamul Kholqil Lazuardy (Jurnal Pengabdian Masyarakat, 2026)
This study is motivated by the low interest and understanding of the younger generation, especially Generation Alpha, toward civil engineering, as well as the importance of integrating educational and spiritual values in character development. The purpose of this study is to improve participants’ knowledge, interest, and awareness of civil engineering while instilling religious values through mosque-based activities during the month of Ramadan. The method used is the Asset-Based Community Development (ABCD) approach, which consists of the stages of discovery, dream, design, define, and destiny. Data collection techniques were carried out through direct observation of participants’ participation, responses, and behavioral changes during the activity. The results of the study indicate that this program significantly improved participants’ understanding of basic civil engineering concepts and their application in daily life. In addition, there was an increase in learning interest, active participation, and participants’ ability to relate civil engineering knowledge to their surrounding environment. From a social and spiritual perspective, the activity also enhanced participants’ awareness of the importance of maintaining public facilities, managing time between gadget use and worship, and strengthening values of togetherness and social care. Overall, this program had a positive impact in increasing knowledge literacy, shaping religious character, and encouraging youth involvement in community-based social activities.